Genomic insights into the serovar prevalence, antimicrobial resistance gene, and genetic diversity of Salmonella enterica in Mexico. - Luis Lozano-Aguirre; Josefina Duran-Bedolla; Juan Téllez-Sosa; Cindy Fabiola Hernández-Pérez; Ismael Hernández-Lucas; Humberto Barrios-Camacho (PLoS ONE)
The research aims to provide insights into the sources of contamination, prevalence of common serovars, determination of sequence types, prediction of genes associated with antimicrobial resistance, and phylogenetic analysis to evaluate genetic diversity and correlations between serovars and sequence types in Salmonella enterica in Mexico. We analyzed 818 publicly accessible whole-genome sequences from Mexico, which included isolates from diverse sources such as poultry, meat, water, and agricultural environments. We identified fifty-seven serovars, of which 19.8% corresponded to S. Infantis, 10.7% to S. Anatum, and 6.6% to S. Newport, representing the most common serovars. Phylogenetic analysis shows a strong correlation between sequence type and serovar. For example, ST32 for S. Infantis and ST64 for S. Anatum show this. However, serovars such as S. Newport possessed considerable genomic diversity, suggesting complex contamination pathways. The analysis showed that many isolates have been identified as multidrug-resistant, exhibiting resistance gene profiles for aminoglycosides, β-lactams, fluoroquinolones, sulfonamides, and tetracyclines. The findings emphasize the importance of identifying contamination sources to monitor the dissemination of multidrug-resistant Salmonella in regions that have significant antibiotic consumption in agriculture and farming, highlighting its global relevance for food safety and public health.